DISKURSUS AGAMA DALAM RUANG PUBLIK MENURUT JÃœRGEN HABERMAS - Gunawan, Leo Agung Srie; Bangun, Nathanio Chris Maranatha (LOGOS, 2019)
Today, the role of religions still exists in the public sphere. Habermas sees that religious citizens tend to give their aspirations in the public sphere in a destructive way. As a result, A religion is considered the cause of crime. Actually, It has a various positive benefits to be brought into the public sphere. Therefore, they can convey aspirations in a more appropriate way, namely through a religious discourse. The religious discourse is an act of discourse, that is a discussion with arguments to reach a rational consensus of the best arguments, in the realm of religion. It involves the religious, the secular, and the citizens. It also faces several challenges such as religious fundamentalism, religious privatization, and political religiofication, but it is very relevant to Indonesia, which has many religions and belief streams. Particularly, it is important to see how the relationship between religion and state in Indonesia in order to should be realized.